Child Abuse Intervention: Reporting Protocols in the New Zealand Health Sector - Jackson, Louisa (Victoria University of Wellington Law Review, 2013)
Reporting child abuse has been the subject of a long running socio-legal debate in New Zealand. Its most recent iteration is the Government’s 2012 proposal to require all agencies working with children to institute protocols for referring maltreatment. However, New Zealand’s health sector already operates under such a regime, with little investigation of its success. This article offers a critical analysis of the sector’s protocol framework. It argues that the protocols have established a detailed and enforceable structure for referring maltreatment, but identifies inconsistencies that risk discrepancies in the treatment of vulnerable children. Accordingly, the article recommends that the framework be rationalised and suggests that the legislative proposal include universal thresholds for referral to avoid replication of this problem on a national scale.